Performance of circular footings on sand by use of multiple-geocell or -planar geotextile reinforcing layers - Moghaddas Tafreshi, S.N.; Sharifi, P.; Dawson, Andrew (Elsevier, 2016)
This paper describes a series of reduced scale tests, at unit gravity, performed on circular footings supported by reinforced sand. Reinforcement by multiple layers of geocell was investigated and performance of the footing was compared to one on the same sandy soil containing multi-layered planar geotextile reinforcement. The comparison used geocell and geotextile layers formed from the same parent geosynthetic material having the same characteristics but with less mass of geocell. Results show that the reinforcements’ efficiency (described in terms of the load carrying and subgrade modulus enhancement) decreased as the number of layers increased. In tests at moderate and low footing settlements, significant improvements in bearing capacity and subgrade modulus were obtained with the application of three layers of geocell. On the whole, multi-layered geocell-reinforced soil provides a more effective and much stiffer system that can deliver greater foundation loads and subgrade modulus, as compared to the multi-layered planar-reinforced soil, even when less parent geosynthetic material is used in the multi-layered geocell arrangement. Furthermore, reinforcement benefit is achievable at settlements as small as 0.2-0.4% of footing diameter for the geocell installations whereas settlements 4 to 5 times larger are needed before benefit is gained from a comparable planar geotextile system. To achieve comparable performances, the multi-layered geocell requires 1/4 to 1/2 the mass of geosynthetic material as needed in the form of a multi-layered planar geotextile reinforcement (depending on the settlement allowable). The multi-layered geocell reinforcement needs considerably less parent geosynthetic (reducing transport and, perhaps supply costs) and reduces the size of reinforcement zone required, consequently reducing excavation and the amount of backfill required.